YUSUF XOS HOJIBNING “QUTADGʻU BILIG” ASARIDAGI IJTIMOIY HAYOTNI TARTIBGA SOLISHGA OID QARASHLAR TAHLILI - Berdaliyeva, Sevara (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
This article analyzes the main problems of the social life of that period, as presented in Yusuf Khos Hajib's work "Kutadgu Bilig", and the author's moral and philosophical views on this issue. The article also presents the thinker's thoughts and observations on good and bad human qualities, choosing friends, the role of science in being a good person, and maintaining justice and stability in society.